Circadian clock–gated cell renewal controls time-dependent changes in taste sensitivity - Toru Matsu-ura; Atsunori Nasu; Suengwon Lee; Naoko Yoshida; Kaoru Matsuura; Masaharu Yasuda; Kae Nakamura; Christian I. Hong; Koji Tsuta (Proceedings of the National Academy of Sciences, 2025)
Circadian regulation of the cell cycle progression generates a diurnal supply of newborn cells to replace those lost in organs and tissues. In this study, we analyzed circadian time-dependent changes in cell types within the mouse tongue epithelium. Using single-cell RNA sequencing, we observed circadian time-dependent changes in the populations of stem/progenitor cells and the differentiated cells in mice tongues. Notably, we observed time-dependent changes in the type II taste cell population, which were abolished by ablation of taste bud stem cells, thereby inhibiting cell proliferation within the taste cell population. Through experiments with taste bud organoids (TBOs), we found a 24-h cell cycle period, which was disrupted by the knockdown of the core-clock gene Bmal1 . In TBOs, both cell divisions and apoptotic cells exhibited circadian time-dependent phenotypes. Interestingly, the time-dependent changes in cell death disappeared in the stem cell–ablated TBOs, indicating that the diurnal supply of newly born cells is essential for the rhythmic cell death phenotype. Additionally, taste tests conducted at different times of the day revealed time-dependent sensitivity changes originating from type II taste cells in mice. These findings suggest that the time-dependent changes in taste cell population are driven by circadian clock–regulated cell cycle progression and control time-dependent physiological regulation in the mouse tongue.